Investigation of trapezius muscle effect using ogawa masterdrive massage chair with electromyogram (EMG) sensor / Wan Safiyyah Nurnajah Wan Ahmad Tajuddin - Wan Safiyyah Nurnajah, Wan Ahmad Tajuddin (2019)
Stress and repetitive movement from non ergonomic work condition are two of the many causes of neck and shoulder pain. One of the modalities for the treatment of neck and shoulder pain is massage therapy . This requires the service of a physiotherapist or a chiropractor which may not always be available. To cater for this demand, newer models of automated massage chairs with better functions and modes are being introduced in the market. The OGAWA Master Dr ive massage chair is one of the latest models of automated massage chairs that incorporates heat or thermotherapy as an added function. This is hoped to better mimic the human hand when delivering massage therapy. This study evaluated the effects of OGAWA Master Drive massage chair on the trapezius muscle by using surface electromyogram (EMG) sensor. Ten subjects with no previous neck and shoulder pain or deformity were subjected to two modes of Sensei massage on OGAWA Master Drive massage chair; with heat and without heat respectively. Surface EMG recordings were taken for baseline, during Sensei massage mode without heat, post massage without heat, post Sensei massage with heat, and pos t massage with heat. The mean average value for EMG amplitudes were tak en and compared. I n eight out of ten subjects, the massage mode with heat yielded bigger EMG amplitude shift than that of without heat. The study also found that four out of ten subjects showed increased amplitude shift from baseline average EMG, reflectin g muscle tension post massage session with heat. The study also found that six out of ten participants preferred having the massage with heat as compared to without heat. Th is is not statistically significant (p > 0.005).